Burnout syndrome and healthy lifestyle among Egyptian physicians: A cross-sectional study - Nehal Mohamed Eisa; Mohamed A. M. El-Tabakh; Nourhan M. Kamal; Sara M. Gharbia; Mahmoud M. Samir; Wajid Syed; Mahmood Basil A. Al-Rawi; Ahmed Essam Abou Warda; Abdelrahman S. H. Refaee (PLoS ONE, 2025)
Introduction The phenomenon of burnout and the lifestyle of physicians significantly influence the delivery of healthcare. Over time, burnout intensifies, negatively impacting professional performance, which in turn leads to decreased quality of treatment, patient satisfaction, and productivity. Additionally, it increases the occurrence of medical mistakes and turnover among physicians. In addition to the direct influence of lifestyle on those components. Aim of the study The purpose of this study is to assess burnout syndrome among Egyptian physicians, as well as to investigate factors that contribute to burnout, especially demographic characteristics, lifestyle patterns, and health habits. Methods A cross-sectional study examined burnout prevalence and determinants among 502 Egyptian physicians in different governorates. An electronic questionnaire was used to collect data for the study. Questionnaire covered socio-demographics, The abbreviated Maslach Burnout Inventory (aMBI), and The Health Lifestyle and Personal Control Questionnaire (HLPCQ). Results Younger physicians under 30 showed higher burnout on emotional exhaustion and depersonalization scales, with significant findings (P = 0.047), (P <  0.01) respectively. Male physicians showed stronger depersonalization than females (P <  0.01). Burnout was higher among residents and fellowship trainees, with significant differences in depersonalization (P = 0.021). PhDs showed decreased burnout with significant outcomes (P = 0.002). Longer-working doctors had increased burnout in depersonalization (P = 0.005). Single doctors were more depersonalized than married ones (P = 0.025). Depersonalization was higher in childless people (P = 0.002). However, non-chronic illness physicians were more emotionally exhausted (P = 0.042). Conclusion These findings highlight the intricate relationship between burnout and lifestyle among physicians. A healthy lifestyle, including diet, routines, social support, and physical activity was linked to reduced burnout, while dietary harm avoidance was negatively correlated. This suggests opportunities to enhance the well-being of medical professionals through lifestyle interventions.